"Cerebellar lesions after low-grade tumor resection can induce memory impairment in children, similar to that observed in patients with frontal lesions". Issue 3 (2nd April 2020) - Starowicz-Filip, Anna; Chrobak, Adrian Andrzej; Kwiatkowski, Stanisław; Milczarek, Olga; Rajtar-Zembaty, Anna Maria
ABSTRACT: The aim of the present study was to specify if cerebellar lesions cause memory impairment in children. The study sample consisted of 44 children with low-grade cerebellar astrocytoma, who underwent surgical treatment and 30 healthy controls, matched with regard to age and sex. Memory was tested using the Rey Auditory Verbal Learning Test AVLT, Corsi Block-Tapping Test, Digit Span, Digit Backwards and Information Subtests from the Wechsler Intelligence Scale for Children-Revised WISC-R (PL). Patients with cerebellar lesions demonstrated memory impairments, similar to those typical for patients with frontal lesions, with auditory and visuospatial working memory deficits, a disorganized learning process without mnemonic strategy (executive dysfunctions) and problems with recalling new material from long-term memory storage, while maintaining good recognition of previously learned material, preserved semantic knowledge and short-term auditory-verbal memory (digit span). Obtained results showed that memory deficits would vary according to the side of the cerebellar lesion, with more pronounced impairment of visuospatial memory tasks accompanying the left-sided cerebellar lesions and worse performance of verbal memory task, observed in the group of patients with right-sided cerebellar lesions. Although the presence of hydrocephalus significantly worsens the memory performance of the children studied, patients with cerebellar lesions without hydrocephalus still present significantly lower memory indicators in the profile described, compared to the control group of healthy children. It confirms the hypothesis that cerebellar lesion alone could result in memory dysfunctions in children.